HISTORIOGRAPHY OF INDIAN CHRISTIANITY AND CHALLENGES OF SUBALTERN METHODOLOGY - Oommen, George (Journal of Dharma, 2003)
The attempt in the following essay is to do a brief appraisal of the historiographical developments since 1970s in the history of Indian Christianity and to highlight some of the pertinent methodological aspects of Subaltern Studies with a view to appreciate it’s implications for the writing of the history of Christianity in India. It should be stated at the outset that this is not an exhaustive study of the historical writings on Indian Christianity, and the sources cited are picked up as indicators of the general trends.